2017
DOI: 10.1108/jchrm-03-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between customer orientation, emotional labour and job burnout

Abstract: Purpose Drawing on the conservation of resources theory, this study aims to apply the emotional labour concept to illustrate about the relationship between customer orientation (CO) and job burnout, further demonstrating how the relationship is established in the hospitality industry. This study intends to find that emotional intelligence moderates the relationship between CO and emotional labour. Design/methodology/approach The study uses descriptive statistical analysis and reliability analysis. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…There are three emotional labor strategies used by recent research studies namely: surface acting, deep acting, and displays of genuine emotions (Diefendorff et al, 2005;Judge et al, 2009;Wu and Shie, 2017;Yoo, 2016). Surface acting refers to fake acting and an attempt to display professionally desired emotions without any change to the inner emotion, and is sometimes defined as "faking in bad faith."…”
Section: Emotional Labormentioning
confidence: 99%
See 3 more Smart Citations
“…There are three emotional labor strategies used by recent research studies namely: surface acting, deep acting, and displays of genuine emotions (Diefendorff et al, 2005;Judge et al, 2009;Wu and Shie, 2017;Yoo, 2016). Surface acting refers to fake acting and an attempt to display professionally desired emotions without any change to the inner emotion, and is sometimes defined as "faking in bad faith."…”
Section: Emotional Labormentioning
confidence: 99%
“…Similarly, a recent study (Ahmad et al, 2019) has reported that surface acting, deep acting, and displays of genuine emotions are positively related to a leader's attitude. Wu and Shie (2017), contended that the Conservation of Resources (COR ) theory dealt with resource gains and losses, and following the arguments of the conservation of resources theory, if an individual is emotionally intelligent he/she can avoid negative emotions, as frontline employees may use their own abilities as resources. Furthermore, Cheung, Tang, and Tang (2011) pointed out that psychological capital moderates the relationship among emotional labor and burnout, as well as job satisfaction.…”
Section: Moderating Role Of Psychological Capitalmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, employees who control their emotions through surface acting may experience more serious psychological conflict and higher levels of internal tension. Furthermore, Wu & Shie (2017) indicated that deep acting plays a positive role in mitigating employees' job stress, while surface acting increases job stress by exhausting employees' emotional resources during service (Lee et al, 2015). Employees who are motivated to comply with organizational display rules and can understand and regulate emotions have a resulting reduction in job burnout.…”
Section: Emotional Labor On Job Burnoutmentioning
confidence: 99%